Revitalization of Rehabilitation Based on Religious Moderation Towards Narcotics Abuse in Class II A Penitentiary Institution of Watampone - Hamzah Hamzah; Satriadi Satriadi; Aswar Anas (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
This study examines the revitalization of religious moderation-based development as a novel approach to rehabilitation within the Penitentiary. Significantly, the formulation of development based on religious moderation is proposed as the latest solution for the rejuvenation and refreshment of rehabilitation programs for drug offenders in Class II A Penitentiary Institution of Watampone. This research falls under the category of exploration and adopts the Participatory Action Research approach, normative juridical approach, empirical juridical approach, and normative theological approach. The findings of the study demonstrate that the revitalization of religious moderation-based development emphasizes indicators of national commitment, such as instilling patriotism, accommodating local culture by revitalizing the concept of self, understanding oneself as the best community (khairu ummah) who, in substance, utilizes sound reasoning as the earth's caretaker or as a representative of God, knowledgeable of good and evil, and reflecting religious moderation through adherence to the constitution and compliance with legislation. This includes refraining from consuming and misusing narcotics, in accordance with the mandate of Law No. 35 of 2009 concerning narcotics.